The systemic therapist’s self as a resource in individual psychotherapy - Brusque Radke, Mariane (2022)
The characteristics of the therapist and the ability of the therapist-patient pair to establish a secure bond are discussed in the scientific literature because they are common factors in psychotherapies and essential for treatment success. Considering this aspect, the objective of this study was to analyze and describe the conceptual assumptions related to the idea of the therapist’s self as a resource that favors the development of the therapeutic alliance and interventions in psychotherapy. This is a study of a narrative review of scientific literature which presents a qualitative analysis of publications related to the therapist’s self. Concepts such as therapist’s attachment field, empathy, therapeutic styles, and attachment theory were found. Based on the results, the historical background, the instrumental propositions found by the authors studied, the elaboration of the concept from different theoretical perspectives and, finally, the alternatives and limitations that research and clinical practice on this field still present, are discussed in the light of the systemic perspective.